2015
DOI: 10.1371/journal.pone.0142178
|View full text |Cite
|
Sign up to set email alerts
|

Competence and Quality in Real-Life Decision Making

Abstract: What distinguishes a competent decision maker and how should the issue of decision quality be approached in a real-life context? These questions were explored in three studies. In Study 1, using a web-based questionnaire and targeting a community sample, we investigated the relationships between objective and subjective indicators of real-life decision-making success. In Study 2 and 3, targeting two different samples of professionals, we explored if the prevalent cognitively oriented definition of decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 73 publications
0
22
0
2
Order By: Relevance
“…Fourth, we examined effects of stress in the afternoon, when DHEA and cortisol levels are both relatively lower than they are in the morning due to diurnal rhythms (Hucklebridge et al, 2005); as such, increases in these hormones may influence decision-making competence differently when baseline levels of these hormones are high. Fifth, although the measure of decision-making competence we used in this study is considered the current gold standard, some research suggests that the predictive utility of this measure could be improved by considering social skills and time orientation as well (Geisler and Allwood, 2015). Sixth, although the percentage of women was equivalent across our stress and control groups, because our sample was approximately two-thirds women we may have lacked statistical power to detect subtle sex differences in stress effects on decision-making competence.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we examined effects of stress in the afternoon, when DHEA and cortisol levels are both relatively lower than they are in the morning due to diurnal rhythms (Hucklebridge et al, 2005); as such, increases in these hormones may influence decision-making competence differently when baseline levels of these hormones are high. Fifth, although the measure of decision-making competence we used in this study is considered the current gold standard, some research suggests that the predictive utility of this measure could be improved by considering social skills and time orientation as well (Geisler and Allwood, 2015). Sixth, although the percentage of women was equivalent across our stress and control groups, because our sample was approximately two-thirds women we may have lacked statistical power to detect subtle sex differences in stress effects on decision-making competence.…”
Section: Discussionmentioning
confidence: 99%
“…Still, we acknowledge the difficulties of defining and measuring quality and encourage future research to address this issue. One possibility may be to use a multifaceted approach and include both subjective (i.e., self-reports) and objective (e.g., normative criteria or client-evaluations) indicators in order to get a more complete picture for the quality concept (see, e.g., Geisler & Allwood, 2015).…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Based on this assumption, the present study approaches decision making in a broad way. This is done by including decision-making competence as well as social orientation and time approach ( Geisler and Allwood, 2015 ) among the factors that may influence decision making. In brief, social orientation designates how a person is aware of, relates, and adapts to other people, whereas time approach designates how a person perceives, approaches, and manages time.…”
Section: Introductionmentioning
confidence: 99%
“…However, research investigating the importance of A-DMC performance in work-life settings is lacking. In fact, only Carnevale et al (2011) and Geisler and Allwood (2015) have attended to this issue. Carnevale et al (2011) showed that A-DMC performance in a sample of U.S. high-level leaders outperformed the overall performance reported for Bruine de Bruin et al’s (2007) U.S. community sample.…”
Section: Introductionmentioning
confidence: 99%